The Heterologous Fibrin Sealant and Aquatic Exercise Treatment of Tendon Injury in Rats - Hidd, S. M.C.M.; Dutra, E. F.; Tim, C. R.; Filho, A. L.M.M.; Assis, L.; Ferreira, R. S. [UNESP]; Barraviera, B. [UNESP]; Amaral, M. M. (My University, 2022)
Acute rupture of the calcaneus tendon is relatively common, usually related to sports practice. In recent years, the number of researches in search of more efficient techniques, which induce the healing process, has been growing. The Fibrin Sealant Derived from Snake Venom (FSDSV) or Heterologous Sealant has been standing out in animal and human application for accelerating the repair of lesions, reducing the likelihood of hemorrhage and infectious diseases and having low production cost. Aquatic exercise also presents itself as an efficient strategy for rehabilitation, reducing pain and edemas, improving muscle properties and enhancing the repair process due to the numerous beneficial effects provided by the liquid medium. The aim of this research is to evaluate the use of fibrin sealant derived from snake venom associated with aquatic exercise in tendon repair. We used 84 rats of the Wistar strain, weighing between 170 and 250 g of weight who underwent surgery to induce partial rupture of the calcaneus tendon. The animals were randomly separated into four experimental groups. The technique used was the application of fibrin sealant and aquatic exercises according to the studied group. There was a greater reduction in the edema of the animals’ paws from the seventh day on in all treatments (p < 0.002), when compared to the control group. After 7 and 14 days of treatment, LE showed a greater reduction in the volume of edema (p = 0.03041) compared to the control. After 21 days, the (LS) showed a greater reduction in edema compared to the control group. It was possible to verify a higher collagen to LSE ratio in the evaluated period after 21 days of treatment. Thus, the heterologous fibrin sealant associated or not with aquatic exercise has a beneficial influence on tendon repair, becoming a propitious technique for future clinical applications.
Keywords: Aquatic exercises; Calcaneus tendon; Edema; Fibrin sealant